Method for regulating and controlling microstructure and pore diameter of hollow fiber ceramic membrane and product obtained by method

By optimizing the spinning slurry and controlling the spinning molding process, the nanoparticles migrate to the surface layer of the ceramic membrane, solving the problem of difficulty in preparing small-pore ceramic ultrafiltration membranes in the prior art, and achieving high separation accuracy and low-cost ceramic membrane preparation.

CN119633612AActive Publication Date: 2025-03-18JINGDEZHEN CERAMIC UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510118217.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-18
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

When preparing ceramic membranes by phase conversion method in the prior art, it is difficult to obtain ceramic ultrafiltration membranes with small pore size and high separation accuracy, and the preparation process is complicated and the cost is high.

Method used

By optimizing the composition of the spinning slurry, introducing surfactants and nanoparticles, designing a combination of internal and external coagulation agents. During the dry/wet spinning molding and phase conversion, the nanoparticles are migrated to the surface of the membrane to form a separation layer with a small pore size.

Benefits of technology

Asymmetric structure hollow fiber ceramic ultrafiltration membrane with small pore size (≤25nm) and narrow pore size distribution range is achieved, which simplifies the preparation process, reduces costs, and improves the separation accuracy of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633612A_ABST
    Figure CN119633612A_ABST
Patent Text Reader

Abstract

The invention discloses a method for regulating and controlling the microstructure and aperture of a hollow fiber ceramic membrane and a product obtained by the method. Based on a phase inversion process of dry / wet spinning forming, a proper surfactant is introduced as an additive by optimizing and reasonably designing the variety and coarse and fine grain composition of ceramic raw materials in spinning slurry; the combination of an inner coagulating agent (core liquid) and an outer coagulating bath (outer coagulating agent) is designed, so that nano-particles are migrated to the outer surface layer of a wet membrane to form a small-particle skin layer in the extrusion molding and phase inversion processes, and the hollow fiber ceramic ultrafiltration membrane with the asymmetric structure, which is small in separation membrane layer aperture (the aperture is less than or equal to 25nm, and the average aperture is less than or equal to 20nm) and narrow in aperture distribution range, is obtained. According to the invention, the problem that the ceramic ultrafiltration membrane with small aperture and high separation precision cannot be prepared by adopting a phase inversion method in the prior art is solved, and the prepared ceramic membrane can better meet the application requirements of fine separation while the membrane preparation process is greatly simplified and the preparation cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic materials, and in particular to a method for regulating the microstructure and pore size of a hollow fiber ceramic membrane and a product obtained therefrom. Background Art

[0002] Compared with organic membranes, ceramic membranes have the advantages of good chemical stability, high mechanical strength, long service life, easy cleaning and regeneration, etc. They can be used in particularly harsh working environments, and therefore are increasingly valued. They have been widely used in important industrial fields such as wastewater treatment, seawater desalination, chemical and energy, biopharmaceuticals and food processing, and have made important contributions to environmental protection, energy conservation and emission reduction, and the upgrading and reconstruction of traditional industries. For traditional multi-channel tubular and flat ceramic membranes, in order to reduce the membrane permeation resistance and improve the membrane separation accuracy, the membrane is generally designed into a multi-layer asymmetric structure, including a large particle support layer that provides mechanical strength, a separation layer formed by the accumulation of small particles, and an intermediate layer that prevents the separation layer particles from leaking into the support body (the intermediate layer is a single layer or multiple layers, and for ultrafiltration / nanofiltration membranes, at least 2 to 3 intermediate layers are required). However, using this type of ceramic membrane prepared by the particle stacking method, it is generally difficult to obtain a separation layer with a narrow pore size distribution range after firing due to the uneven particle size of the ceramic powder. At the same time, it is necessary to undergo multiple impregnation coating and multiple high-temperature firing processes to obtain an asymmetric structure membrane, which greatly increases the preparation cost of the ceramic membrane. The cumbersome preparation process is also likely to lead to an increase in membrane defects, affecting the quality stability and separation accuracy of the ceramic membrane.

[0003] In order to effectively solve the above-mentioned key problems that restrict the development of ceramic membrane technology, improve membrane separation performance and reduce the cost of membrane preparation and application, in recent years, the asymmetric hollow fiber ceramic membrane prepared by the phase inversion method has received great attention. Compared with the traditional multi-channel tubular and flat ceramic membranes prepared by particle accumulation, the phase inversion method can be used to prepare asymmetric microtubular membranes through dry / wet spinning one-step molding and one-time high-temperature sintering, and the membrane tube wall is thin, which can greatly simplify the preparation process and reduce the preparation cost and raw material cost. In addition, the hollow fiber ceramic membrane also has the advantages of high membrane packing density and large effective separation area per unit volume of membrane, and it is easy to realize the miniaturization of membrane separation equipment. When the prior art uses the phase inversion method to prepare ceramic membranes, a single type of ceramic powder is generally used to mix with a polymer binder and a solvent to prepare a spinning slurry. After molding and high-temperature sintering, only a microfiltration membrane with a separation layer pore size mainly distributed in 0.1-1.0μm (average pore size greater than 0.1μm) can be obtained, and the pore size distribution range of the membrane is wide, resulting in low membrane separation accuracy, which is still difficult to meet the requirements of fine filtration separation. With the current existing technology, it is still impossible to prepare ceramic ultrafiltration membranes with small pore size and high separation accuracy through phase inversion method. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for regulating the microstructure and pore size of a hollow fiber ceramic membrane. Based on the phase inversion process of dry / wet spinning, the ceramic raw material type and coarse and fine particle grading in the spinning slurry are optimized and reasonably designed, and a suitable surfactant is introduced as an additive. The combination of an internal coagulant (core liquid) and an external coagulation bath (external coagulant) is designed so that the nanoparticles migrate to the outer surface of the wet membrane during the extrusion molding and phase inversion process to form a small particle cortex, thereby obtaining an asymmetric structure hollow fiber ceramic ultrafiltration membrane with a small pore size (pore size ≤ 25nm, average pore size ≤ 20nm) and a narrow pore size distribution range, so as to break through the problem that the prior art cannot prepare a ceramic ultrafiltration membrane with a small pore size and high separation accuracy by using the phase inversion method, and greatly simplify the membrane preparation process and reduce the preparation cost, so that the prepared ceramic membrane can better meet the requirements of fine separation applications. Another purpose of the present invention is to provide a product obtained by using the above-mentioned method for regulating the microstructure and pore size of a hollow fiber ceramic membrane.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for regulating the microstructure and pore size of a hollow fiber ceramic membrane, comprising the following steps:

[0007] (1) Preparation of ceramic base powder

[0008] The composition of the ceramic base material is 80-90wt% of 3mol% yttria-stabilized zirconia micropowder and 10-20wt% of nano-oxide powder; wherein the nano-oxide powder is aluminum oxide, silicon oxide or titanium oxide powder, and the average particle size of the 3mol% yttria-stabilized zirconia micropowder is more than 20 times the average particle size of the nano-oxide powder; the ceramic base material is uniformly mixed by dry method in a mixer according to the composition ratio to obtain ceramic base material powder;

[0009] (2) Preparation of spinning slurry

[0010] Adding polyethersulfone (PES) particles into N-methyl-2-pyrrolidone (NMP) solvent and dissolving to obtain a polymer solution; adding a nonionic surfactant to the polymer solution and dissolving it, and then adding the ceramic base material powder and stirring and mixing to obtain a spinning slurry; the contents of the polyethersulfone, N-methyl-2-pyrrolidone, nonionic surfactant, and ceramic base material powder in the spinning slurry are 7-10wt%, 36-40wt%, 1-2.5wt%, and 48-55wt%, respectively;

[0011] (3) Dry / wet spinning

[0012] The spinning slurry is loaded into a spinning molding device, after vacuum degassing, extruded through a spinneret with an inner tube under a nitrogen pressure of 0.2 to 1 bar, immersed in an external coagulation bath for curing and molding, and taken out after molding and naturally dried at room temperature to obtain a ceramic membrane blank;

[0013] (4) High temperature sintering

[0014] The ceramic membrane blank is first heated to 800-850°C at 1-2°C / min in a nitrogen atmosphere and kept warm for 1-2 hours, and then heated to 1100-1300°C at 2-4°C / min in an air atmosphere and kept warm for 2-5 hours; then cooled to 300-500°C at 5°C / min, and finally cooled naturally to obtain a small-pore hollow fiber composite ceramic ultrafiltration membrane with an average pore size of the separation membrane layer ≤20nm.

[0015] Furthermore, in step (1) of the present invention, the average particle size of the 3 mol% yttria-stabilized zirconia powder is 0.5-1.5 μm, and the average particle sizes of the aluminum oxide, silicon oxide, and titanium oxide powders are 30-100 nm, 20-50 nm, and 5-20 nm, respectively; preferably, the silicon oxide powder is 1.5 mol% magnesium oxide-doped silicon oxide powder.

[0016] In the above scheme, in step (1) of the present invention, dry mixing is performed by a mixer for 3 to 4 hours. In step (2), the molecular weight of polyethersulfone is 10,000 to 50,000; the nonionic surfactant is a combination of polyoxyethylene sorbitan monolaurate (Tween 20) or polyoxyethylene sorbitan monopalmitate (Tween 40) and polyethylene glycol (PEG600 or PEG800).

[0017] In the above scheme, the internal coagulant (core liquid) in the inner tube of step (3) of the present invention is water, and its outflow rate is 30-80 mL / min; the extrusion speed of the spinning slurry is 1.7-2.2 cm / s, and after extrusion, it passes through an air distance of 2-3 cm and enters the external coagulation bath (external coagulant); the external coagulation bath is an alcohol aqueous solution with an ethanol content of 70-80 vol%, and the immersion time is 12-24 h.

[0018] The product obtained by the above-mentioned method for regulating the microstructure and pore size of the hollow fiber ceramic membrane is a hollow fiber composite ceramic ultrafiltration membrane with an asymmetric structure, wherein the inner side of the membrane is a large-pore porous inner skin layer formed by the accumulation of small particles, the middle is a support layer formed by the accumulation of large particles and having finger-like holes, and the outer side of the membrane is a small-pore porous outer skin layer formed by the accumulation of nanoparticles as a separation membrane layer. The hollow fiber composite ceramic ultrafiltration membrane has an average pore size of 5 to 20 nm, a maximum pore size not exceeding 1.5 times the flat pore size, a thickness of 0.5 to 2 μm, a membrane porosity of 45 to 52.5%, a bending strength of 90 to 116 MPa, and a pure water flux of 151 to 447 LMH / bar.

[0019] The present invention has the following beneficial effects:

[0020] (1) The present invention creatively adopts the matching of ceramic powder particles with large differences in particle size and density. During the dry / wet spinning and phase transformation process, under the synergistic effect of the shear force generated by the nitrogen pressure extrusion molding and the mass transfer exchange between the external coagulant and the solvent and its surfactant in the slurry, the highly hydrophilic lightweight nanoparticles in the slurry can quickly migrate to the surface of the extruded wet membrane, gradually enrich on the outer surface of the hollow fiber ceramic membrane precursor, and form a separation layer composed of small particles. By using a hydrophilic surfactant composite additive with a specific molecular weight and HLB value range, while reducing the viscosity and lubricity of the slurry, under the combined effect of the extrusion shear force and the external coagulant / solute mass transfer exchange, the nanoparticles are driven to migrate rapidly to the surface of the membrane precursor. In this process, an alcohol aqueous solution with weakened gelling ability is used as an external coagulation bath to delay the solidification of the wet membrane surface layer, ensuring that enough nanoparticles migrate to the surface layer to enrich and form a nanoparticle membrane layer. In addition, by combining the heat treatment process of first heat treatment in a protective atmosphere and then high-temperature sintering in air, the growth of grains of the membrane separation layer components can be inhibited and the porosity of the separation layer can be increased, thereby obtaining a highly permeable small-pore hollow fiber ceramic ultrafiltration membrane.

[0021] (2) The method of the present invention can be used to prepare a hollow fiber ceramic ultrafiltration membrane separation layer with a small pore size and high porosity, and its pore size is easy to control and has a narrow distribution range (the maximum pore size of the separation membrane layer does not exceed 1.5 times the average pore size), thereby meeting the requirements for efficient and high-precision separation of different substances. The method of the present invention can also be used to prepare a hollow fiber ceramic microfiltration membrane with a narrow pore size distribution range and high separation accuracy.

[0022] (3) The ceramic ultrafiltration membrane is prepared by the method of the present invention. Since some small particles exist between the joints of large particles, the large particles can be promoted to form stronger neck connections during the high-temperature sintering process, which is beneficial to improving the mechanical strength of the ceramic membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings:

[0024] Figure 1 Schematic diagram of the microstructure of the hollow fiber composite ceramic ultrafiltration membrane of the present invention;

[0025] Figure 2 This is a SEM image of the hollow fiber composite ceramic ultrafiltration membrane prepared in the present invention (a: cross section; b: outer surface). DETAILED DESCRIPTION

[0026] Embodiment 1:

[0027] This embodiment provides a method for regulating the microstructure and pore size of a hollow fiber ceramic membrane, and the steps are as follows:

[0028] (1) Preparation of ceramic base powder

[0029] The composition of the ceramic base material is 85wt% of 3mol% yttria-stabilized zirconia powder with an average particle size of 1μm and 15wt% of aluminum oxide (Al2O3) powder with an average particle size of 80nm; according to the composition ratio, dry mixing is carried out in a mixer for 3h to obtain ceramic base material powder;

[0030] (2) Preparation of spinning slurry

[0031] Adding polyethersulfone (PES E2010) particles with a molecular weight of 10000 to 50000 into N-methyl-2-pyrrolidone (NMP) solvent, stirring and dissolving to obtain a uniform polymer solution; adding nonionic surfactants polyoxyethylene sorbitan monolaurate (Tween 20) and polyethylene glycol (PEG800) to the polymer solution, stirring and dissolving to obtain a spinning slurry; the contents of the polyethersulfone, N-methyl-2-pyrrolidone, polyoxyethylene sorbitan monolaurate, polyethylene glycol, and ceramic base material powder in the spinning slurry are 8wt%, 40wt%, 1wt%, 1wt%, and 50wt%, respectively;

[0032] (3) Dry / wet spinning

[0033] The spinning slurry is loaded into a stainless steel slurry tank in a spinning forming device, and after vacuum degassing, it is extruded at a speed of 2 cm / s through a spinneret with an inner tube (the outer diameter and inner diameter are 2.3 mm and 1.0 mm, respectively) under a nitrogen pressure of 0.5 bar. During the extrusion process, the flow rate of the inner coagulant (core liquid) water flowing out of the inner tube is controlled by a flow meter to be 40 mL / min. After extrusion, after passing through an air distance of 2 cm, it enters an external coagulation bath (an alcohol aqueous solution with an ethanol content of 80 vol%) and is immersed for 24 hours for curing and forming. After forming, it is taken out and naturally dried at room temperature to obtain a ceramic membrane blank;

[0034] (4) High temperature sintering

[0035] The ceramic membrane blank was first heated to 800°C at 1.5°C / min in a nitrogen atmosphere and kept for 1 hour, and then heated to 1250°C at 3°C / min in an air atmosphere and kept for 4 hours; then cooled to 500°C at 5°C / min, and finally cooled naturally to obtain a 3YSZ / Al2O3 hollow fiber composite ceramic ultrafiltration membrane with an average pore size of 19 nm in the outer separation membrane layer.

[0036] Embodiment 2:

[0037] This embodiment provides a method for regulating the microstructure and pore size of a hollow fiber ceramic membrane, and the steps are as follows:

[0038] (1) Preparation of ceramic base powder

[0039] The composition of the ceramic base material is 90wt% of 3mol% yttria-stabilized zirconia powder with an average particle size of 0.8μm and 10wt% of 1.5mol% magnesium oxide-doped silicon oxide (SiO2) powder with an average particle size of 30nm; according to the composition ratio, dry mixing is carried out in a mixer for 4h to obtain ceramic base material powder;

[0040] (2) Preparation of spinning slurry

[0041] Adding polyethersulfone (PES E2010) particles with a molecular weight of 10000 to 50000 into N-methyl-2-pyrrolidone (NMP) solvent, stirring and dissolving to obtain a uniform polymer solution; adding nonionic surfactants polyoxyethylene sorbitan monopalmitate (Tween 40) and polyethylene glycol (PEG600) to the polymer solution, stirring and dissolving to obtain a spinning slurry; the contents of the polyethersulfone, N-methyl-2-pyrrolidone, polyoxyethylene sorbitan monopalmitate, polyethylene glycol, and ceramic base powder in the spinning slurry are 7.5wt%, 40wt%, 1wt%, 1.5wt%, and 50wt%, respectively;

[0042] (3) Dry / wet spinning

[0043] The spinning slurry is loaded into a stainless steel slurry tank in a spinning forming device, and after vacuum degassing, it is extruded at a speed of 2 cm / s through a spinneret with an inner tube (the outer diameter and inner diameter are 2.3 mm and 1.0 mm, respectively) under a nitrogen pressure of 0.6 bar. During the extrusion process, the flow rate of the inner coagulant (core liquid) water flowing out of the inner tube is controlled by a flow meter to be 50 mL / min. After extrusion, after passing through an air distance of 2 cm, it enters an external coagulation bath (an alcohol aqueous solution with an ethanol content of 80 vol%) and is immersed for 24 hours for curing and forming. After forming, it is taken out and naturally dried at room temperature to obtain a ceramic membrane blank;

[0044] (4) High temperature sintering

[0045] The ceramic membrane blank was first heated to 800°C at 1.5°C / min in a nitrogen atmosphere and kept warm for 1 hour, and then heated to 1150°C at 3°C / min in an air atmosphere and kept warm for 3 hours; then cooled to 300°C at 5°C / min, and finally cooled naturally to obtain a 3YSZ / SiO2 hollow fiber composite ceramic ultrafiltration membrane with an average pore size of 9nm in the outer separation membrane layer.

[0046] Embodiment three:

[0047] This embodiment provides a method for regulating the microstructure and pore size of a hollow fiber ceramic membrane, and the steps are as follows:

[0048] (1) Preparation of ceramic base powder

[0049] The composition of the ceramic base material is 83wt% of 3mol% yttria-stabilized zirconia powder with an average particle size of 0.6μm and 17wt% of titanium oxide (TiO2) powder with an average particle size of 18nm; according to the composition ratio, dry mixing is carried out in a mixer for 4h to obtain ceramic base material powder;

[0050] (2) Preparation of spinning slurry

[0051] Adding polyethersulfone (PES E2010) particles with a molecular weight of 10000 to 50000 into N-methyl-2-pyrrolidone (NMP) solvent, stirring and dissolving to obtain a uniform polymer solution; adding non-ionic surfactants polyoxyethylene sorbitan monopalmitate (Tween 40) and polyethylene glycol (PEG600) to the polymer solution, stirring and dissolving to obtain a spinning slurry; the contents of the polyethersulfone, N-methyl-2-pyrrolidone, polyoxyethylene sorbitan monopalmitate, polyethylene glycol, and ceramic base powder in the spinning slurry are 7wt%, 38wt%, 1wt%, 1.5wt%, and 52.5wt%, respectively;

[0052] (3) Dry / wet spinning

[0053] The spinning slurry is loaded into a stainless steel slurry tank in a spinning forming device, and after vacuum degassing, it is extruded at a speed of 2 cm / s through a spinneret with an inner tube (the outer diameter and inner diameter are 2.3 mm and 1.0 mm, respectively) under a nitrogen pressure of 0.7 bar. During the extrusion process, the flow rate of the inner coagulant (core liquid) water flowing out of the inner tube is controlled by a flow meter to be 50 mL / min. After extrusion, after passing through an air distance of 2 cm, it enters an external coagulation bath (an alcohol aqueous solution with an ethanol content of 75 vol%) and is immersed for 24 hours for curing and forming. After forming, it is taken out and naturally dried at room temperature to obtain a ceramic membrane blank;

[0054] (4) High temperature sintering

[0055] The ceramic membrane blank was first heated to 800°C at 1.5°C / min in a nitrogen atmosphere and kept for 1 hour, and then heated to 1100°C at 3°C / min in an air atmosphere and kept for 5 hours; then cooled to 500°C at 5°C / min, and finally cooled naturally to obtain a 3YSZ / TiO2 hollow fiber composite ceramic ultrafiltration membrane with an average pore size of 5nm in the outer separation membrane layer.

[0056] like Figure 1 and Figure 2 As shown, the hollow fiber composite ceramic ultrafiltration membrane prepared by the present invention presents an asymmetric structure, and its cross section is mainly composed of inner and outer skin layers and a support layer with long finger-like holes in the middle, that is, the inner side of the membrane is a large-pore porous inner skin layer formed by the accumulation of small particles, the middle is a support layer formed by the accumulation of large particles and having finger-like holes, and the outer side of the membrane is a small-pore porous outer skin layer formed by the accumulation of nanoparticles and serving as a separation membrane layer; the surface of the outer separation membrane layer presents a uniform porous structure.

[0057] The structural parameters and physical properties of the small-pore hollow fiber composite ceramic ultrafiltration membrane prepared in the embodiment of the present invention are shown in Table 1. Ultrafiltration membranes with different pore sizes all have the advantages of narrow pore size distribution range, high porosity and high pure water permeation flux. The ultrafiltration membrane separation layer prepared by the present invention has a high open porosity, so that its pure water permeation flux is more than twice that of a multilayer structure ceramic ultrafiltration membrane with similar pore size prepared by a conventional method.

[0058] Table 1 Structural parameters and physical properties of the hollow fiber composite ceramic ultrafiltration membrane prepared in the embodiment of the present invention

[0059]

Claims

1. A method for regulating the microstructure and pore size of a hollow fiber ceramic membrane, characterized in that The following steps are involved: (1) Preparation of ceramic base powder The composition of the ceramic base material is 80-90wt% of 3mol% yttria-stabilized zirconia micropowder and 10-20wt% of nano-oxide powder; wherein the nano-oxide powder is aluminum oxide, silicon oxide or titanium oxide powder, and the average particle size of the 3mol% yttria-stabilized zirconia micropowder is more than 20 times the average particle size of the nano-oxide powder; the ceramic base material is uniformly mixed by dry method in a mixer according to the composition ratio to obtain ceramic base material powder; (2) Preparation of spinning slurry The polyethersulfone particles are added to N-methyl-2-pyrrolidone solvent to obtain a polymer solution after dissolving; a non-ionic surfactant is added to the polymer solution to dissolve, and then the ceramic base material powder is added and stirred to obtain a spinning slurry; the contents of the polyethersulfone, N-methyl-2-pyrrolidone, non-ionic surfactant and ceramic base material powder in the spinning slurry are 7-10wt%, 36-40wt%, 1-2.5wt% and 48-55wt% respectively; (3) Dry / wet spinning The spinning slurry is loaded into a spinning molding device, after vacuum degassing, extruded through a spinneret with an inner tube under a nitrogen pressure of 0.2 to 1 bar, immersed in an external coagulation bath for curing and molding, and taken out after molding and naturally dried at room temperature to obtain a ceramic membrane blank; (4) High temperature sintering The ceramic membrane blank is first heated to 800-850°C at 1-2°C / min in a nitrogen atmosphere and kept warm for 1-2 hours, and then heated to 1100-1300°C at 2-4°C / min in an air atmosphere and kept warm for 2-5 hours; then cooled to 300-500°C at 5°C / min, and finally cooled naturally to obtain a small-pore hollow fiber composite ceramic ultrafiltration membrane with an average pore size of the separation membrane layer ≤20nm.

2. The method for controlling the microstructure and pore size of a hollow fiber ceramic membrane according to claim 1, characterized in that: In the step (1), the average particle size of the 3 mol% yttria-stabilized zirconia powder is 0.5-1.5 μm, and the average particle sizes of the aluminum oxide, silicon oxide, and titanium oxide powders are 30-100 nm, 20-50 nm, and 5-20 nm, respectively.

3. The method for controlling the microstructure and pore size of a hollow fiber ceramic membrane according to claim 1 or 2, characterized in that: The silicon oxide powder is 1.5 mol % magnesium oxide doped silicon oxide powder.

4. The method for controlling the microstructure and pore size of a hollow fiber ceramic membrane according to claim 1, characterized in that: In the step (1), dry mixing is performed by a mixer for 3 to 4 hours.

5. The method for controlling the microstructure and pore size of a hollow fiber ceramic membrane according to claim 1, characterized in that: The molecular weight of the polyethersulfone in step (2) is 10,000 to 50,000; the nonionic surfactant is a combination of polyoxyethylene sorbitan monolaurate or polyoxyethylene sorbitan monopalmitate and polyethylene glycol.

6. The method for controlling the microstructure and pore size of a hollow fiber ceramic membrane according to claim 1, characterized in that: The internal coagulant in the inner tube of step (3) is water, and its outflow rate is 30-80 mL / min; the extrusion speed of the spinning slurry is 1.7-2.2 cm / s, and after extrusion, it passes through an air distance of 2-3 cm and enters the external coagulation bath; the external coagulation bath is an alcohol aqueous solution with an ethanol content of 70-80 vol%, and the immersion time is 12-24 h.

7. A product obtained by using the method for controlling the microstructure and pore size of a hollow fiber ceramic membrane according to any one of claims 1 to 6, characterized in that: It is a hollow fiber composite ceramic ultrafiltration membrane with an asymmetric structure. The inner side of the membrane is a large-pore porous inner layer formed by the accumulation of small particles, the middle is a support layer formed by the accumulation of large particles and has finger-like holes, and the outer side of the membrane is a small-pore porous outer layer formed by the accumulation of nanoparticles and serves as a separation membrane layer.

8. The product according to claim 7, characterized in that: The average pore size of the surface separation membrane layer of the hollow fiber composite ceramic ultrafiltration membrane is 5-20nm, the maximum pore size does not exceed 1.5 times the flat diameter pore size, the thickness is 0.5-2μm, the membrane porosity is 45-52.5%, the bending strength of the ceramic ultrafiltration membrane is 90-116MPa, and the pure water flux is 151-447LMH / bar.

Citation Information

Patent Citations

  • Ceramic membrane having asymmetric structure, and preparation method of ceramic membrane

    CN105771675A

  • Method for preparing gas-solid separation ceramic membrane based on phase inversion method and spraying method

    CN117504619A

  • High-permeability hollow fiber ceramic membrane

    CN202136924U

  • Filter apparatus

    JP2005270810A